PRELIMINARY PHYTOCHEMICAL SCREENING AND IN VITRO ANTI-MICROBIAL ACTIVITY OF ETHANOLIC EXTRACT OF STEMS OF THE PLANT TAGETES ERECTA L. (FAMILY-ASTERACEAE) - Ali, Jafar; Shil, Dibyendu (International Journal of Current Pharmaceutical Research, 2018)
Objective: To estimate the anti-microbial activity of ethanolic extract of Tagetes erecta L. (family-Asteraceae) in association with phytochemical analysis. Methods: The ethanolic extract of the stems of TageteseErecta L. was prepared and investigate for phytochemical constituents using standard methods. Antimicrobial activity of ethanolic extract of has been carried out against one Gram positive bacteria-Staphylococcus aureus and one Gram negative bacteria-Escherichia coli, and the antifungal activity of the plant extract was evaluated on Candida albicans species. The testing was done by the disc diffusion method to visualize the zone of inhibition of ethanolic extract was compared with that of standard drug i.e., Ciprofloxacin for anti-bacterial activity and Terbinafine for anti-fungal activity. The MIC was determined by the microdilution method (Cup-plate method). Results: The present investigation shows the phytochemical analysis, antimicrobial activity of the ethanolic extract of the stems of Tagetes erecta L. Various phytochemical analysis confirmed the presence of alkaloids, saponin glycosides, flavonoids, phenol, proteins and amino acids, cardiac glycosides, steroids, tanin and phenolic compounds. The anti-microbial activity of the ethanolic extract of the plant showed significant results against all three of the test organisms in compare to the standard drugs. Conclusion: The present study concluded that ethanolic extract of-of the stems of Tagetes erecta L. Proved the existence of phytochemical constituents. The ethanolic extract of the plant was found to possess promising antimicrobial activity when compared with the standards and it can be useful for the development of the antibiotics.